English Learning Outcomes Based on Indonesian Enacted Current Curriculum in the Perspective of Vocational Students’ Need: A Critical Discourse Analysis - Rihatmi Rihatmi; Margana Margana; Riris Handayani; Fani Nabila Titania; Sharizan Sharizan (STAI Hubbulwathan Duri, 2025)
English learning outcomes in vocational education must align with enacted curriculum policies and the specific needs of vocational students. In Indonesia, the Merdeka Curriculum (Freedom to Learn Curriculum) 2022 sets national educational standards, including English language policies. This study examines the alignment between these policies and the English for Specific Purposes (ESP) approach, which is essential for vocational students preparing for future professions. This qualitative study employs Critical Discourse Analysis (CDA) to analyze pedagogical discourse at the policy level. Content analysis of government documents on English learning outcomes was conducted, alongside interviews with teachers and students to gather practical insights. Findings indicate that while the Merdeka Curriculum provides general learning outcomes, vocational educators must adapt these to meet students' specific needs. Teachers play a crucial role in integrating relevant themes, practical assignments, and industry-related activities into English instruction. However, challenges remain in effectively implementing ESP due to curriculum constraints and a lack of contextualized materials. The study highlights the need for flexibility in curriculum implementation, emphasizing a balance between national policies and vocational students' professional requirements. Teachers require support in curriculum adaptation to enhance pedagogical strategies and ensure meaningful learning experiences. This research provides critical insights into the impact of policy changes on English learning in vocational schools. It underscores the importance of contextualized instruction and suggests improvements in policy implementation to better serve vocational students’ career aspirations.